Exploring student diversity: Entrepreneurial Intent & Self-efficacy, Personal Characteristics, Creativity, and the Link to Performance in Entrepreneurship and Innovation Training - Beukel, Karin (Improving University Science Teaching and Learning, 2023)
Summary. Teaching Innovation and Entrepreneurship for natural science or business students is a complex process, where not only knowing the theories of entrepreneurship, the elements of a business plan and financial planning is needed, but also skills in identifying opportunities in the market or exploring own creativity to come up new ideas for future startups can become crucial. Using applied teaching therefore also becomes and exploration of students own personal characteristics. In this paper I investigate the broader skillset and characteristics of the students enrolled in an innovation and entrepreneurship course. To understand the students I focus on studying the variation in a number of innovation and entrepreneurship related factors, namely entrepreneurial intent, entrepreneurial self-efficacy, personal characteristics (i.e. their profile in terms of extraversion/introversion, intuiting/sensing, thinking/feeling, and perceiving/judging.), and their creativity. The results show a highly varied group of students. The work is explorative and based on data gathered at University of Copenhagen (UCPH), the data analysis mainly consists of descriptive data and correlations. Finally I reflect on how the findings direct future teaching in entrepreneurship and innovation.